Shallow water acoustic techniques to investigate transitional environments: A case study over Boka Kotorska Bay. (October 2018) - Ligi, Marco; Bortoluzzi, Giovanni; Giglio, Federico; Del Bianco, Fabrizio; Ferrante, Valentina; Gasperini, Luca; Ravaioli, Mariangela
Highlights: Shallow-water non-invasive acoustic techniques to explore transitional environments. CHIRP data forward modeling and envelope inversion to estimate earth reflectivity. The seafloor morphology and geology of Boka Kotorska Bay. Abstract: The eastern border of the Adriatic Sea shows several examples of transitional areas marked by fragmented coastlines, islands and coastal bays. Bays and estuaries interact with the main basin influencing it and being influenced by it in terms of circulation patterns and freshwater supply. Coastal and transitional areas represent highly dynamic, rapidly changing environments subjected to multiple interactions with the marine-land-fluvial systems related processes. Processes such as coastal erosion, seawater intrusion, pollution and sediment transport and deposition affect these areas. One of the most important transitional areas along the entire Adriatic coast, from both an environmental and a socio-economic viewpoint, is the bay of Boka Kotorska, where the sea enters inland for over 20 km. The Bay is located along the Montenegro margin and is part of a ria coastal system surrounded by high mountains part of the Dinaric range. Boka Kotorska Bay includes three major basins, connected by two narrow straits with a maximum depth of 67 m. Despite its historical and geostrategic role the morphology and geology of the Bay is poorly known. Coastal areas are among the most urbanized and populated regions; for these reasons the application of geophysical minimally invasive methods are required in order to collect geological and morphological data. High resolution seismic reflection techniques such as CHIRP systems, adopting a non-impulsive source wavelet, are ideal to carry out seismic surveys in transitional environments. Here, we present a detailed description of this system in order to furnish the mathematical basis for forward modelling. Moreover, we outline a procedure to estimate the earth reflectivity by inversion of the recorded signal envelope (reflection strength), i.e., the standard way to store CHIRP data. Reflection strength data alone, characterizing the signal power as a function of time, do not retain all the characteristics of the recorded signal they represent and thus, cannot be further processed and hardly be compared with results from forward modeling. New high resolution multibeam and seismic reflection data collected in the Boka Kotorska Bay reveal unknown details of present-day morphologies and sedimentary infilling geometries. Several processes are involved in shaping the bay and its seafloor. Our results show that the observed morphologies are due to the interaction at different timescales of climate, water circulation, sealevel changes, erosion, sedimentation and tectonics constrained by the geological and structural setting of the area.